Singkawang City Government’s Strategy to Increase Knowledge Dimension of The Human Development Index (HDI) in 2023 - Millavathiy, Riri; Muradi, Muradi; Mulyawan, Rahman (Universitas Muhammadiyah Gorontalo, 2025)
Singkawang Mayor's Regulation Number 11.1 of 2023 concerning Changes to the Singkawang City Regional Development Plan for 2023 - 2026 with one of the objectives being